Structural controls on mud volcano vent distributions: Examples from Azerbaijan and Lusi, east Java - Roberts, K.; Davies, R.; Stewart, S.; Tingay, Mark (Geological Society Publishing House, 2011)
Structural mapping, nearest neighbour and two-point azimuth statistical analysis of mud volcano vent distributions from nine examples in Azerbaijan and the Lusi mud volcano in east Java are described. Distributions are non-random, forming alignments subparallel to faults within anticlines, ring faults, conjugate faults and detachment faults; this finding confirms a spatial relationship and supports a model for subsurface flow along these features as well as showing fractionation at depth. As fracture and fault orientations are related to structures such as anticlines and the in situ stress state they are therefore predictable. We use vent distributions in Azerbaijan, where the structural geology is well constrained, to propose what controls the distribution of 169 vents at the Lusi mud volcano. This mud volcano system shows evidence for initial eruptions along a NE-SW trend, parallel to the Watukosek fault, changing to eruptions that follow east-west trends, subparallel to regional fold axes. Our analysis indicates that regions east and west of the Lusi mud volcano are more likely to be affected by new vents than those to the north and south, owing to probable onset of elongate caldera collapse within a 10 km diameter of the central vent.